PEMUNGUTAN RETRIBUSI PELAYANAN PASAR BERDASARKAN PERATURAN DAERAH NOMOR 8 TAHUN 2017 TENTANG PERUBAHAN ATAS PERATURAN DAERAH KOTA PEKANBARU NOMOR 6 TAHUN 2012 TENTANG RETRIBUSI PELAYANAN PASAR DI KOTA PEKANBARU - Melyanta Siringo Ringo; Gusliana HB; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
This study related with Collection Retribution Service Markets in Pekanbaru City thatare regulated in Regulation area Number 8 of 2017 About Change on Pekanbaru CityRegulations Number 6 of 2012 About Retribution Service Market in Pekanbaru City and iswhich is source income original Pekanbaru City area. In reality on the ground service marketin Pekanbaru City experience a number of constraint covers collection retribution serviceunfinished market reach the target and low level awareness Required retribution servicemarket in Pekanbaru City.Type study this is law sociological that is the research you want see correlationAmong law and society, so capable disclose effectiveness take effect law in society. Study thisdone at the Service Industry and Pekanbaru City Trade, Market Cik Puan Market LabuhBaru and the Pekanbaru City DPRD. Source of data used are primary data and secondarydata, techniques data collection in study this is with observation, questionnaire, interview andstudy library, and concluded with method think deductive.From result research, concluded that, First, the collection retribution service marketin Pekanbaru City based on Regional Regulation Number 8 of 2017 concerning Change onPekanbaru City Regulations Number 6 of 2012 About Retribution Service Market inPekanbaru City not optimal. Second, the factors that influence collection retribution servicemarket covers factor supporter is law, while factor blocker is lack of source power human,lack awareness law Required retribution, enforcement law, budget. third, Effort from ServiceIndustry and Pekanbaru City Trade is identify subject and object retribution, increase sourcepower human, examination and supervision retribution, do socializing, implementing penaltyfor violator Required retribution, and enhancement service market .Keywords: Collection -Retribution - Retribution Service Market